Duane's retraction syndrome in a cohort of South African children a 20 year clinic based review - Steyn, Anna (Division of Ophthalmology, 2020)
OBJECTIVES: To describe the clinical features of Duane’s retraction syndrome in a cohort of South African children and analyse subtypes for ethnic differences. METHODS: Retrospective case series of 120 patients seen in the period from 1997 to 2017 at the Red Cross War Memorial Children’s Hospital. RESULTS: Of the 120 patients, Type 1 was present in 76 (64%) of cases, with Type 2 in 27 (23%) and Type 3 in 16 (13%).Type 2 was most common in black children (54%), while Type 1 predominated in mixed race (68%) and white children (94%). A female predominance was seen in white children (69%) and mixed race children (59%), while there was a male predominance amongst black children (62.5%) Left involvement was the most common (44%), followed by right (41%) and bilateral involvement (14%).The average age of presentation was 2,85 years. A positive family history of squints or Duane’s was present in 6 (0,5%). Congenital systemic abnormalities were present in 12 (1%) and congenital ocular abnormalities in 2 (0.4%). Squint in primary position was present in 57 (46%), of which 39% had esotropia and 61% exotropia. Squint was more common in black children (71%) than in mixed race (39.4%) and white children (41%). An abnormal head position was present in 59 (50%) and was most common in Type 2 (67%). Up and downshoots were seen in 58 (48.3%). Ametropia was found in 94 (79%), and of these 88 (93,6%) were hyperopic and 6 (6.4%) myopic. Amblyopia was present in 15 (12.5%). Surgery was performed in 41(34%). CONCLUSION: This study is the first to provide robust data on the profile of paediatric DRS in the 3 main South African ethnic groups, and shows clear ethnic differences in DRS. In black patients, males are more often affected, the proportion with Type 2 DRS is more frequent, and surgery is required more often. Further population-based studies on the epidemiology of DRS in children are needed to clarify the role of race as a potential risk factor.